Reduction of bubble cavitation by modifying the diffraction wave from a lithotripter aperture - Zhou, Yufeng (2013)
Purpose: A new method was devised to suppress the bubble cavitation in the lithotripter focal zone to reduce the propensity of shockwave-induced renal injury.